2015
DOI: 10.18666/tpe-2015-v72-i5-4641
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Physical Education Teachers' Computer Literacy on Technology Use in Physical Education

Abstract: Teachers' computer literacy has been identified as a factor that determines their technology use in class. The aim of this study was to investigate the relationship between physical education (PE) teachers' computer literacy and their technology use in PE. The study group consisted of 57 high school level in-service PE teachers. A survey was used to assess the PE teachers' computer literacy and instructional technology and media use in PE. Quantitative statistical procedures were performed to analyze the data.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 32 publications
0
17
0
8
Order By: Relevance
“…For teachers, computer literacy includes the skills that allow them to use computers comfortably as instructional tools (Watt, 1980). Teachers’ computer literacy can affect their technology use in class (Kretschmann, 2015).…”
Section: Teacher Perceptions Of Technologymentioning
confidence: 99%
“…For teachers, computer literacy includes the skills that allow them to use computers comfortably as instructional tools (Watt, 1980). Teachers’ computer literacy can affect their technology use in class (Kretschmann, 2015).…”
Section: Teacher Perceptions Of Technologymentioning
confidence: 99%
“…The research to date has identified the ability and actual usage of technology to be low among teachers (Altun, 2013;Hsu, 2010;Levin & Wadmany, 2008) and PE teachers (Kretschmann, 2012;Tearle & Golder, 2008;Thomas & Stratton, 2006;Yaman, 2008;Yilmaz, Ulucan, & Pehlivan, 2010). Teachers mostly use the internet to attract students' attention (Lee & Tsai, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Au cours de la dernière décennie, il y a eu une croissance exponentielle des cours de formation à distance en éducation physique au Brésil (Anversa et al, 2017;Lazzarotti Filho et al, 2015) contrairement à la tradition du domaine ancrée sur le savoir-faire et les pratiques et expériences corporelles. Il convient de noter que la formation des enseignants d'éducation physique a été imprégnée, comme cela est le cas pour d'autres domaines, des technologies numériques, surtout dans les débats sans portée pratique (Kretschmann, 2015;Leight et Nichols, 2012).…”
Section: Introductionunclassified
“…La pertinence de cette recherche se trouve dans le fait qu'elle documente et diffuse le processus de transition de ces formateurs d'un modèle d'enseignement présentiel à un enseignement à distance, médiatisé par les technologies. Il est à noter qu'il y a peu d'études empiriques dans le domaine des technologies numériques et de l'éducation physique et, en particulier, sur le point de vue des enseignants de cette discipline (Kretschmann, 2015).…”
Section: Introductionunclassified